NONFORMAL ADULT EDUCATION: PUBLIC AND PRIVATE TEACHING SECTORS - Butvilienė, Jūratė (Acta Paedagogica Vilnensia, 2013)
The paper deals with adult nonformal education peculiarities, stressing the obvious gap between social and human capital. Besides, nonformal education as an additional part of formal education is mainly kept in mind. The main goal of this research is to analyze and present the differences between public and private teaching sectors regarding nonformal adult education on adult learners’ and nonformal education organizers’ levels. Thus, some statistically meaningful findings on those differences are revealed, mainly dealing with adults‘ motivation, experienced obstacles, selection of teaching courses / programs, reasons to participate / not participate, and other demographic features discussed and compared within this survey. Based on the quantitative research, in the way presented in this paper, some statistical evidence is discussed, especially comparing public and private adult teaching / learning sectors. The main differences are seen through: i) choosing teaching programs, ii) reasons to participate / avoid, iii) experiences, obstacles / struggles of nonformal education, or even iv) learning intentions along with adults’ aspirations.
Keywords: education; nonformal adult education; private and public teaching sectors